2013
DOI: 10.1002/2013jc009228
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of the meridional overturning circulation at 34.5°S: Results from two pilot boundary arrays in the South Atlantic

Abstract: [1] Data from two boundary arrays deployed along 34.5 S are combined to produce the first continuous in situ time series observations of the basin-wide meridional overturning circulation (MOC) ) after a 10 day lowpass filter is applied. Much of the variability in this $20 month record occurs at periods shorter than 100 days. Approximately two-thirds of the MOC variability is due to changes in the geostrophic (baroclinic plus barotropic) volume transport, with the remainder associated with the direct wind-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 72 publications
(102 reference statements)
8
115
0
Order By: Relevance
“…The Southwest Atlantic MOC (SAM) array was first deployed at 34.5 • S in March 2009 to capture the meridional flow of the western boundary currents, with the primary aim of making long-term measurements of the western boundary flows associated with the MOC (Meinen et al, 2012(Meinen et al, , 2013b. The ultimate long-term goal was also for the SAM array to be a cornerstone for the South Atlantic MOC Basin-wide Array (SAMBA) at 34.5 • S, which is coming to fruition with parallel deployments occurring on the eastern boundary in 2013 and 2014 (e.g., Ansorge et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Southwest Atlantic MOC (SAM) array was first deployed at 34.5 • S in March 2009 to capture the meridional flow of the western boundary currents, with the primary aim of making long-term measurements of the western boundary flows associated with the MOC (Meinen et al, 2012(Meinen et al, , 2013b. The ultimate long-term goal was also for the SAM array to be a cornerstone for the South Atlantic MOC Basin-wide Array (SAMBA) at 34.5 • S, which is coming to fruition with parallel deployments occurring on the eastern boundary in 2013 and 2014 (e.g., Ansorge et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…This has mostly been a matter of convenience and proximity, not a reflection on scientific importance, as theoretical work and numerical models have suggested that variations in the South Atlantic may be critical to the stability and flow of the overall MOC system (e.g., Dijkstra, 2007;Drijfhout et al, 2011;Garzoli and Matano, 2011;Garzoli et al, 2013;Buckley and Marshall, 2016). Only in the past few years have observations been collected to study the MOC and/or the DWBC in the South Atlantic region, beginning with repeated upper ocean expendable bathythermograph (XBT) transects (e.g., Garzoli and Baringer, 2007;Dong et al, 2009Dong et al, , 2014 and full-depth hydrographic sections (e.g., Speer 2003, 2007;, and later adding continuous moored observations at a few locations including 11 • S (Hummels et al, 2015) and 34.5 • S (Meinen et al, 2012(Meinen et al, , 2013b. Gridded data sets from Argo float profiles in the upper 2000 m of the water column and satellite altimetry measurements have also been brought to bear on the meridional flows in the South Atlantic (e.g., Schmid, 2014;Dong et al, 2015;Majumder et al, 2016), providing important information about latitudinal variations of the MOC.…”
Section: Introductionmentioning
confidence: 99%
“…Through the two arrays, RAPID and OSNAP, we will have a better understanding of the Atlantic MOC. A third array is still in early stages of deployment South Atlantic (South Atlantic Meridional Overturning Circulation, SAMOC) [57]. This transport estimate at the southern boundary of the Atlantic will …”
Section: (B) a Wider View Of Circulationmentioning
confidence: 99%
“…[47]). The combination of findings from RAPID and OSNAP, along with the continuing efforts to continuously monitor the meridional circulation at southern latitudes [3,6,46], will soon provide new insights into ocean dynamics connectivity and the associated evolution of the Atlantic OHC.…”
Section: Observational Insights Into the Regional Dynamics: An Atlantmentioning
confidence: 99%